Measurement of the associated production of a single top quark and a Z boson in pp collisions at, root s=13 TeV - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Del Valle, A. Escalante; Flechl, M.; et al. (Elsevier B.V., 2018)
A measurement is presented of the associated production of a single top quark and a Z boson. The study uses data from proton-proton collisions at, root s = 13 TeV recorded by the CMS experiment, corresponding to an integrated luminosity of 35.9 fb(-1). Using final states with three leptons (electrons or muons), the tZq production cross section is measured to be sigma (pp -> tZq -> Wbl(+)l(-)q) = 123(-31)(+33)(stat)(-23)(+29)(syst) fb, where l stands for electrons, muons, or tau leptons, with observed and expected significances of 3.7 and 3.1 standard deviations, respectively. C) 2018 The Author. Published by Elsevier B.V.
Keywords: SM; Single top; Cross section; tZq